Design of Incu Analyzer for IoT-based Baby Incubator Calibration - Septiana, Silvi Dwi; Syaifudin, Syaifudin; Maghfiroh, Anita Miftahul; Huynh, Phuoc-Hai (Jurnal Teknokes, 2023)
Incubator Analyzer is a calibration tool that measures baby incubators' temperature, mattress temperature, humidity, airflow, and sound level. This research aims to design an "Incu Analyzer for IOT-based Baby Incubator Calibration (Chamber Temperature)" tool with an LCD and Thingspeak integration. The design of this calibration tool involves the baby incubator chamber temperature parameters, namely T1, T2, T3, T4, and T5, which are measured using the DS18B20 sensor. The ESP32 microcontroller is employed to leverage the IoT system, and Wi-Fi is used for IoT communication. The ESP32 processes data collected from the DS18B20 temperature sensor and displays it on the LCD and Thingspeak. This tool is tested by comparing the incubator analyzer module with a standard measuring instrument, INCU II. The temperature parameter yielded the smallest error value of -0.059293% at T5 with a setting temperature of 36°C and the largest error value of -0.0254188% at T2 with a setting temperature of 35°C. In conclusion, after conducting a comprehensive study of the literature and planning, it can be affirmed that the "Incu Analyzer Design for IOT-Based Baby Incubator Calibration" tool functions as planned, demonstrating its efficacy as an IoT-based Incubator Analyzer. This research has successfully developed an IoT system that utilizes Wi-Fi to transmit data and display reading results on Thingspeak, which significantly facilitates users in monitoring the calibration process.